2014
DOI: 10.1128/jvi.00972-14
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation as an Epigenetic Consequence of Epstein-Barr Virus Infection of Immortalized Keratinocytes

Abstract: The oral cavity is a persistent reservoir for Epstein-Barr virus (EBV) with lifelong infection of resident epithelial and B cells. Infection of these cell types results in distinct EBV gene expression patterns regulated by epigenetic modifications involving DNA methylation and chromatin structure. Regulation of EBV gene expression relies on viral manipulation of the host epigenetic machinery that may result in long-lasting host epigenetic reprogramming. To identify epigenetic events following EBV infection, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
117
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 58 publications
9
117
0
1
Order By: Relevance
“…Intact BAC clones were rescued from the pools of EBV-infected keratinocytes, indicating that the SNU719-BAC and YCCEL1-BAC viruses were episomally maintained (data not shown). This observation corresponds well with a previous report that telomerase-immortalized oral keratinocytes could be infected with Burkitt's lymphoma-derived EBV strain Akata, and EBV genomes were subsequently lost from the infected cells (30). In contrast, when HDK1-K4DT cells were infected with a derivative of EBV strain B95-8 [BART(ϩ) B95.8 virus (14)], the majority of hygromycin-resistant cells were GFP negative (Fig.…”
Section: Resultssupporting
confidence: 68%
“…Intact BAC clones were rescued from the pools of EBV-infected keratinocytes, indicating that the SNU719-BAC and YCCEL1-BAC viruses were episomally maintained (data not shown). This observation corresponds well with a previous report that telomerase-immortalized oral keratinocytes could be infected with Burkitt's lymphoma-derived EBV strain Akata, and EBV genomes were subsequently lost from the infected cells (30). In contrast, when HDK1-K4DT cells were infected with a derivative of EBV strain B95-8 [BART(ϩ) B95.8 virus (14)], the majority of hygromycin-resistant cells were GFP negative (Fig.…”
Section: Resultssupporting
confidence: 68%
“…S1), although staining was visible in the normal surrounding cells. Interestingly, NOKs (telomerase-immortalized NOKs), which support an unusually low level of lytic EBV promoter methylation in comparison with other EBVinfected epithelial cell lines (16,17), had easily detectable 5hmC-modified DNA, even in the less differentiated basal cells (Fig. 1C).…”
mentioning
confidence: 87%
“…Lytic viral gene expression following EBV infection of normal epithelial cells likely reflects the ability of the other EBV immediate-early (IE) protein, BRLF1 (R), to efficiently activate unmethylated lytic viral promoters. We recently showed that overexpression of R, but not Z, induces lytic EBV gene expression and replication in a latently infected telomerase-immortalized normal oral keratinocyte (NOKs) line, where the lytic viral promoters remain largely unmethylated (16,17). R activates lytic gene expression by binding to R-response elements (RREs) with a consensus sequence of GNCCN 9 GGNG (N 9 is a nine-nucleotide spacer region that can be any sequence) (18) or indirectly by interacting with cellular transcription factors (13).…”
mentioning
confidence: 99%
“…The different transgenomic clones differ in their profiles. Viewed under the perspective of previously published investigations from our [5][6][7]16] and from other [11][12][13][14] laboratories, it is apparent that the insertion of foreign DNA into an established mammalian genome can lead to genome-wide destabilizations of cellular transcription and methylation patterns. We have not yet conducted a systematic investigation into the epigenetic trans effects of transgenome size, its From the sum total of all our previous investigations on this topic, we conclude that the integrations of Ad12, bacteriophage λ or plasmid DNA as well as the currently used pC1-5.6 plasmid have all led to alterations of methylation and transcriptional profiles in the recipient cells [5][6][7].…”
Section: Resultsmentioning
confidence: 99%
“…In Epstein-Barr virus (EBV)-transformed human lymphoblastoid cell lines, in EBV-infected cells [11,12] or in human macrophages carrying integrated HIV-1 proviral genomes [13], cellular DNA methylation and transcription patterns have been significantly altered. In induced pluripotent human stem cells with multiple integrated foreign genes, genome-wide alterations of CpG methylation profiles have been described [14].…”
mentioning
confidence: 99%